The Business Opportunities and Constraints within the Printing and Graphic Arts Industry: A Study on Sylhet City - Muzib, Md. Moniruzzaman; Rahman, Md. Mizanur (Global Disclosure of Economics and Business, 2014)
This paper investigates the growing competitive printing and graphic arts industry in Sylhet focusing on the investment process, employment opportunity, government support, and the others crucial factors of market that are responsible in determining the industry volume through some statistical analysis. By looking on the opportunity and constraints of this industry, it addresses the preference of the customers as well as the limitation and potential for growth. Statistical significant association was tested by tools like descriptive analysis through the primary data, SWOT analysis etc. to examine the relationship of the considered variables and the prospect and constrictions of this industry has been analyzed with recommendation. JEL Classification Code: M00